Did child obesity decline after 2016 food regulations in Chile? - Paul T. von Hippel; Francisca Bogolasky Fliman (Pan American Health Organization, 2024)
We estimated trends in the prevalence of obesity and overweight among Chilean primary and secondary students before and after Chile's 2016 regulations on the marketing and availability of foods high in energy, total sugars, sodium, or saturated fat. We used data from Chile's Survey of Nutrition, which measured the body mass index (BMI) of students in government-funded schools. Using BMI thresholds defined by the World Health Organization, we calculated the prevalence of overweight and obesity for each year from 2013 to 2019 among students attending pre-kindergarten (age 4 years), kindergarten (age 5 years), first grade (6 years), and ninth grade (14 years). In ninth grade students, overweight and obesity prevalence rose by 2 percentage points over the 3 years after introduction of the 2016 regulations. In pre-kindergarten, kindergarten, and first grade, overweight and obesity fell 1 to 3 percentage points 1 year after the regulations were introduced, but rebounded to previous levels the next year. Chile's food regulations were not followed by a sustained decline in obesity in primary- and secondary-school students. Future research should examine whether and how children in Chile and other countries maintain high levels of overweight and obesity despite food regulations designed to reduce consumption of obesogenic foods and beverages.